PENGEMBANGAN LKS BIOLOGI BERBASIS PEMECAHAN MASALAH DI SMP N 3 SUNGAYANG - Ningsih, Ayu Puspita; Trisoni, Ridwal; Khaira, Kuntum (Jurnal Pembelajaran MIPA, 2014)
The research was aimed to get a product LKS of Biology based on problem solving was valid and practical. The kind of this research was researh of development. This research used 4-D model developing, they were define, design, develop, disseminate. Procedure of research have been done in three phase, they are, face behind, prototype and assessment. Based on the research have done that LKS Biology based on problem solving was valid through validity test in some validator. Result of practicality test through ingquiry very practical, meanwild practicality test have been done through observation and inetrview, modul was said practical after process in descriptive technique. So, quality of develpoment result product was valid and practical based on result of validity test and practicality test have done.Key words : development, LKS, Problem Solving,Â  biological learning